Guidelines for stem cell research and therapy - Malaysia. Kementerian Kesihatan. Bahagian Perkembangan Perubatan (Bahagian Perkembangan Perubatan, Kementerian Kesihatan Malaysia, 2009)
"The 2nd edition of the National Guidelines for Stem Cell Research and Therapy, prepared by Medical Development Division of the Ministry of Health, has comprehensively revised the first edition of the same book to facilitate researchers and clinicals involved in stel cell research and therapy" -- foreword